STUDYING THE ROLE OF SOCIAL MEDIA IN ADDRESSING MISINFORMATION, CYBERBULLYING AND PRIVACY VIOLATIONS - Singh, Radha; Singh, Mili (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines the role of social media platforms in addressing misinformation, cyberbullying and privacy violations. As online platforms become increasingly integrated into modern culture, the prevalence of these malpractices has increased, causing potential harm to individuals and broader social structures. The paper employs data analysis techniques, including content and thematic analysis of qualitative data as well as both descriptive and inferential measures. The results aim to provide a comprehensive understanding of the social impact of misinformation on social media and the efficacy of virtual platforms in addressing these issues. This research aims to provide valuable insights into the consequences of misconduct on virtual platforms, exploring their potential in reducing lies, cyberbullying and privacy violations. By identifying effective strategies, the study aims to inform policy and practice, contributing to the development of a safer and more responsible virtual environment.